2005
DOI: 10.1021/bi050068x
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium-Sensor Guanylate Cyclase Activating Protein Type 2 Specific Site in Rod Outer Segment Membrane Guanylate Cyclase Type 1

Abstract: The rod outer segment membrane guanylate cyclase type 1 (ROS-GC1), originally identified in the photoreceptor outer segments, is a member of the subfamily of Ca(2+)-modulated membrane guanylate cyclases. In phototransduction, its activity is tightly regulated by its two Ca(2+)-sensor protein parts, GCAP1 and GCAP2. This study maps the GCAP2-modulatory site in ROS-GC1 through the use of multiple techniques involving surface plasmon resonance binding studies with soluble ROS-GC1 constructs, coimmunoprecipitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 31 publications
3
52
2
Order By: Relevance
“…Contrary to the models hypothesized elsewhere (32)(33)(34), we recently demonstrated that the docking interface(s) for both GCAP1 and GCAP2 is encoded by a region, Arg 488 -Arg 851 , containing the KHD and dimerization domain of RetGC1 (27) rather than its C terminus and transmembrane-proximal portions, making two independent docking sites for different GCAPs (33,35). In the present study, we tested how mutations (site-directed or naturally occurring) specifically in the RetGC1 dimerization domain affected binding of GCAPs.…”
contrasting
confidence: 67%
“…Contrary to the models hypothesized elsewhere (32)(33)(34), we recently demonstrated that the docking interface(s) for both GCAP1 and GCAP2 is encoded by a region, Arg 488 -Arg 851 , containing the KHD and dimerization domain of RetGC1 (27) rather than its C terminus and transmembrane-proximal portions, making two independent docking sites for different GCAPs (33,35). In the present study, we tested how mutations (site-directed or naturally occurring) specifically in the RetGC1 dimerization domain affected binding of GCAPs.…”
contrasting
confidence: 67%
“…Bicarbonate binds to the CCD. For illustrative purposes, GCAP1, GCAP2, S100B, and neurocalcin ␦ are shown bound to the ROS-GC1 (65)(66)(67)(68)(69). In reality, neurocalcin ␦ is not expressed in photoreceptors, and the ROS-GC1 dimer binds either two GCAP1s or two GCAP2s.…”
Section: Discussionmentioning
confidence: 99%
“…The mOrangeRetGC1VenusN chi- Fig. 2; the a max values for stimulation by GCAPs in the absence or presence of 1 and 2 M M26R GCAP1 only slightly change for stimulation by GCAP1 (27,26, and 25 nmol of cGMP/min/mg, respectively) or GCAP2 (22,21, and 19 nmol of cGMP/min/mg, respectively), but the K 1/2GCAP increased in the presence of M26R GCAP1 for wild type GCAP1 (1.5, 4, and 6.7 M, respectively) and GCAP2 (1.7, 4.7, and 7.4 M, respectively). The Hill coefficient increased for GCAP1 (from 1.17 in the absence to 1.53 in the presence of 2 M M26R GCAP1) and for GCAP2 (from 1.14 in the absence to 1.54 in the presence of 2 M M26R GCAP1).…”
Section: Gcap1 and Gcap2 Compete For Binding To The Same Retgc1mentioning
confidence: 94%
“…6, top), and thus eliminated the entire putative Tyr 1016 -Ser 1103 GCAP2 binding site (26,27), with a non-homologous sequence: the N-terminal portion of the YFP, VenusN (49). The chimera protein lacking the putative GCAP2 binding site was then tested for co-localization with GCAP2 in a cell-based binding assay (Fig.…”
Section: Gcap1 and Gcap2 Compete For Binding To The Same Retgc1mentioning
confidence: 99%
See 1 more Smart Citation